Analysis of Boezem Kalidami Pump Capacity To Cope With Floods East Surabaya Region - R. Dandy Jurindra Pratama; Adi Prawito; Farida Hardaningrum (NAROTAMA UNIVERSITY, Indonesia, 2021)
Kalidami river has a length of 4.2 kilometers with a stretch of channels from the Airlangga, Manyar, Kertajaya, to Kejawan Putih Tambak areas. Boezem Kalidami is located at the downstream of the Kalidami river which is also equipped with a pump house and a water gate. The Log Pearson III method produces a design rainfall of 127.38 mm / 24 hours so that the rainfall is very heavy. So that it will produce a maximum flood discharge of 40.3 m³ / s and when compared to the capacity of Boezem Kalidami which is only 49,440 m³, Boezem Kalidami will fill very quickly. Coupled with the total efficient pump capacity of only 15.33 m³ / s, Boezem is only able to accommodate the first 2 hours and an overflow of 1.58 meters from Boezem Kalidami's riverside at 2.14.